2015
DOI: 10.1681/asn.2014090939
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Fibrosis Restricts Osmotic Water Transport in Encapsulating Peritoneal Sclerosis

Abstract: Encapsulating peritoneal sclerosis (EPS) is a rare but severe complication of peritoneal dialysis (PD) characterized by extensive fibrosis of the peritoneum. Changes in peritoneal water transport may precede EPS, but the mechanisms and potential predictive value of that transport defect are unknown. Among 234 patients with ESRD who initiated PD at our institution over a 20-year period, 7 subsequently developed EPS. We evaluated changes in peritoneal transport over time on PD in these 7 patients and in 28 match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(123 citation statements)
references
References 53 publications
3
110
2
8
Order By: Relevance
“…The combination of functional and structural analysis of the membrane of patients with EPS demonstrated that reduced osmotic water transport is directly related to the degree of fibrosis and to changes in collagen density and structure in the peritoneal interstitium (88), in line with predictions based on the serial pore-membrane/fiber matrix and distributed models (94)(95)(96). Of note, the low osmotic (50).…”
Section: Prevention Of Epssupporting
confidence: 63%
“…The combination of functional and structural analysis of the membrane of patients with EPS demonstrated that reduced osmotic water transport is directly related to the degree of fibrosis and to changes in collagen density and structure in the peritoneal interstitium (88), in line with predictions based on the serial pore-membrane/fiber matrix and distributed models (94)(95)(96). Of note, the low osmotic (50).…”
Section: Prevention Of Epssupporting
confidence: 63%
“…The use of human biopsy samples has been approved by the Ethical Review Board of the Cliniques universitaires Saint-Luc. Adequacy of each peritoneal specimen, peritoneal fibrosis, collagen volume fraction, and collagen structure were assessed as previously described (7,16). Immunofluorescence was performed using purified rabbit anti-von Willebrand factor (DAKO, Glostrup, Denmark) and polyclonal rabbit anti-human AQP1 (Chemicon International, Temecula, CA, USA) antibodies (16).…”
Section: Methodsmentioning
confidence: 99%
“…However, recent analysis with biopsy samples from EPS patients showed that AQP-1 expression did not change between EPS and long-term PD or uremic peritoneum, instead of significant upregulated VEGF and endothelial nitric oxide synthase (eNOS) with increasing vascular density in EPS cases [89]. In this study, SMC thickness and collagen volume fraction showed significant correlation with UF failure and sodium sieving, but not with small solute transport, and these pathological parameters were significantly severe in EPS than in other groups [89]. This meaningful study showed that UF capacity and sodium sieving could be used as a predicting risk factor for EPS, however, SMC thickness and collagen in EPS cases should have been measured from existing peritoneum (HPS lesion) excluding newly formed membrane of EPS (the study included EPS membrane in the pathological analysis), because the EPS membrane does not reflect functional test histories before the lesion is formed.…”
Section: Pathological Findings Of Pd Associated Infectious Peritonitismentioning
confidence: 98%
“…Aquaporin (AQP)-1 null mice study showed that AQP-1 expressed in peritoneal endothelium plays an essential role in water permeability and UF during PD [88]. However, recent analysis with biopsy samples from EPS patients showed that AQP-1 expression did not change between EPS and long-term PD or uremic peritoneum, instead of significant upregulated VEGF and endothelial nitric oxide synthase (eNOS) with increasing vascular density in EPS cases [89]. In this study, SMC thickness and collagen volume fraction showed significant correlation with UF failure and sodium sieving, but not with small solute transport, and these pathological parameters were significantly severe in EPS than in other groups [89].…”
Section: Pathological Findings Of Pd Associated Infectious Peritonitismentioning
confidence: 99%